Cases and materials on the European Convention on Human Rights - Mowbray, Alastair (Butterworths, 2001)
For many years undergraduate and postgraduate students have found it an increasing challenge to cope with the extensive, complex and lengthy jurisprudence emanating from the Strasbourg institutions. Cases and Materials on the European Convention on Human Rights provides a selection of the leading jurisprudence, together with commentary, on the major rights enshrined in the Convention. Chapters on the institutions and remedies available at the European level have also been included, in order to give the reader a full understanding of how the European Court system operates